A new species of shrimp-goby genus Cryptocentrus (Teleostei:Gobiidae) from the Philippines - Chen, I-Shiung; Liao, Yun-Chih; Shao, Kwang-Tsao (Zootaxa, 2025)
A new marine shrimp-goby of the genus Cryptocentrus was collected from the coastal waters of Luzon, the Philippines. This new species, Cryptocentrus aureostriatus sp. nov., can be well distinguished from other congeneric species by the following unique combination of features: (1) second dorsal fin I/11; anal fin I/10; pectoral fin 16; (2) squamation: longitudinal scale rows 60–62; transverse scale rows 24; predorsal scale rows 17; (3) normal vertebral count 26; and (4) colouration in life: body generally creamy yellow, body with about eight major brown cross-bars; nape with two brown major bars; caudal fin base with a deep, vertical brown bar; head with three major oblique, parallel golden yellow stripes; snout tip with one short orange bar; the posterior tip of opercle with one yellow mark; first dorsal fin with three major oblique yellow stripes; second dorsal fin translucent with several yellow stripes; anal fin creamy yellow to pale white and unmarked. A description of the new species and a brief comparison with related species in the Indo-Pacific region will be reported in this paper.